2023
DOI: 10.3390/brainsci13050801
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Correlates of Treatment Response to Transcranial Magnetic Stimulation in Bipolar Depression: A Systematic Review

Abstract: Transcranial magnetic stimulation (TMS) has become a promising strategy for bipolar disorder (BD). This study reviews neuroimaging findings, indicating functional, structural, and metabolic brain changes associated with TMS in BD. Web of Science, Embase, Medline, and Google Scholar were searched without any restrictions for studies investigating neuroimaging biomarkers, through structural magnetic resonance imaging (MRI), diffusion tensor imaging (DTI), functional MRI (fMRI), magnetic resonance spectroscopy (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Experts in the field believe that there is a need to move beyond these biomarkers and to investigate novel predictors of treatment response in depression, such as measures of DNA methylation or protein expression, in combination with digital methods of phenotyping and machine learning [ 114 , 115 , 116 , 117 ]. In contrast, most studies of YBI in depression have used biological correlates that have already been extensively investigated and found to be of limited specificity and predictive power [ 52 , 56 , 92 ]. Similarly, though neuroimaging and cognitive findings have yielded the best effect sizes for prediction of antidepressant response [ 52 ], only three of the studies reviewed here made use of these markers [ 76 , 80 , 82 ].…”
Section: Critical Analysis Of the Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experts in the field believe that there is a need to move beyond these biomarkers and to investigate novel predictors of treatment response in depression, such as measures of DNA methylation or protein expression, in combination with digital methods of phenotyping and machine learning [ 114 , 115 , 116 , 117 ]. In contrast, most studies of YBI in depression have used biological correlates that have already been extensively investigated and found to be of limited specificity and predictive power [ 52 , 56 , 92 ]. Similarly, though neuroimaging and cognitive findings have yielded the best effect sizes for prediction of antidepressant response [ 52 ], only three of the studies reviewed here made use of these markers [ 76 , 80 , 82 ].…”
Section: Critical Analysis Of the Review Findingsmentioning
confidence: 99%
“…Most studies of treatment response in depression have evaluated biomarkers in relation to antidepressant drug therapy. However, these markers may also be useful in evaluating the response to other forms of treatment, such as electroconvulsive therapy [ 55 ], repetitive transcranial magnetic stimulation [ 56 ], and psychotherapies such as cognitive behavioral therapy (CBT) [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has related altered brain metabolism to the key symptoms of Major Depressive Disorder (MDD) and conditions associated with this disease [1,2], as well as stress-related pathologies [3][4][5] and other neuropsychiatric conditions sharing clinical features with MDD [6][7][8][9][10]. Conversely, early studies have shown that 70% of patients diagnosed with mitochondrial disorders met the diagnostic criteria for mental disorders, including depression and cognitive problems [11].…”
Section: Introductionmentioning
confidence: 99%
“…Anhedonia, decreased sensitivity to a reward, is considered a key feature of MDD [65,66]. Unlike another core symptom of this disorder, depressed mood [9,10,67], it can be induced and measured in small rodents [67,68]. In MDD patients, hedonic deficit was previously established to be associated with cognitive symptoms [41,42], impaired plasticity in the hippocampus [67,68], and other key neurochemical and cellular correlates of MDD [67,68].…”
Section: Introductionmentioning
confidence: 99%